2018
DOI: 10.12659/msm.911022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pathological Prognostic Stage and Anatomic Stage Groups According to the Updated Version of the American Joint Committee on Cancer (AJCC) Breast Cancer Staging 8th Edition

Abstract: BackgroundWe compared pathological prognostic stage (PPS) with anatomic stage (AS) groups according to the updated version of breast cancer staging of the American Joint Committee on Cancer (AJCC) 8th Edition.Material/MethodsWe evaluated 353 breast cancer patients initially treated with surgery. AS and PPS were performed by evaluating the pathological data of the patients according to the AJCC 8th Edition breast cancer updated version. Stages and survival rates between the 2 staging systems were evaluated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…The results obtained confirm that integration of tumour load (size and presence of node involvement) with tumour type (grade and prognostic factors) leads to an increased number of patients classified as stage I, as previously reported. 16,17 Furthermore, in line with other studies, 18,19 we found that stage I according to PS clearly identifies a group of patients with a more favourable outcome, distinguishing them from other patients with lesions classified as stage II or III and providing more accurate prognostic information compared with AS.…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained confirm that integration of tumour load (size and presence of node involvement) with tumour type (grade and prognostic factors) leads to an increased number of patients classified as stage I, as previously reported. 16,17 Furthermore, in line with other studies, 18,19 we found that stage I according to PS clearly identifies a group of patients with a more favourable outcome, distinguishing them from other patients with lesions classified as stage II or III and providing more accurate prognostic information compared with AS.…”
Section: Discussionsupporting
confidence: 90%
“…PS IIIB and IIIC from AS IIB had significant differences in DFS (χ 2 =5.628, p=0.014) and OS (χ 2 =6.037, p=0.018). Ibis et al [22] also found patients with AS IIB breast cancer restaged to different PS groups in a cohort of 353 Turkish patients, with a significant difference in 10-year DFS among restaged PS groups. Thus, we confirmed that PS system provided more accurate information on prognosis than AS system in patients with TNBC, especially in AS IIB group.…”
Section: Discussionmentioning
confidence: 86%
“…Studies have indicated that the inclusion of these biological factors in the traditional anatomic staging system would be beneficial [ [3] , [4] , [5] , [6] , [7] , [8] ], and accordingly, some changes were made in the 8th AJCC breast cancer staging system [ 1 , 2 , 7 , 8 ], which is the first staging system to incorporate biological factors into the TNM staging system. The new prognostic staging system is considered to be a significantly superior tool for predicting survival outcome as compared to the previous one, and its prognostic benefits have been validated in several studies [ [9] , [10] , [11] , [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%